AN ANALYSIS OF IDIOM EXPRESSIONS IN NOVEL â€œMARY POPPINSâ€ BY P.L. TRAVERS - Saputri, Nia Liska; Irfan Hadi, Irfan (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2021)
By reading novels students can simultaneously learn several language skills. Vocabulary skills related to other language skills. Vocabulary skills are related to the ability to write and read as well as speak. However, not many teachers do not use novels as a teaching medium. In the novel, there are idiom expressions that are very important for the development of students' English skills. This research method uses qualitative methods, with literature study research techniques. The document being studied is a novel entitled Marry Poppins. The results of the study found several types of idioms, 36% of phrasal verbs, 22% of prepositional phrases, 14% of idioms with verbs as keywords, 11% of idioms with nouns as keywords, 11% of idioms with adjective as keywords and 6 idiomatic pairs. %